Doing it right: imperatives of thinking strategically about IT and the Internet - Hassan, Arif; Hassan, Sajid (Association for Social Engineering, Research & Training (PATNA), 2009)
Spending on Information Technology in business organization has increased ten fold over the past few years. Consequently, the expenditure has often been marred by misuse of funds, resources and infrastructure. Top managements are often unaware of IT jargons and they allow expenditure on unnecessary or obsolete IT activities and projects. Problems like improper human-IT interface resulting into employees becoming techno shy, improper mformation flow have become quite common. Design of an Improper IT infrastructure can lead to unnecessary bureaucratic steps thereby losing productivity at the same time, IT department complams of unrealistic user requirements. expectation and scope-creep. It is against this background that the present paper attempts to identify the problems generally associated with IT spending within the organization and possible remedies by referring to researches done by prominent scholars within the field.